The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/978-3-319-78105-1_29
|View full text |Cite
|
Sign up to set email alerts
|

Data Retrieval = Text Retrieval?

Abstract: Due to the comparatively more recent emergence of data retrieval systems than text-based search engines, the former have still yet to attain similar maturity in terms of standards and techniques. Most of the existing solutions for data retrieval are more or less makeshift adaptations of text retrieval systems rather than purpose-built solutions specially designed to cater to the particular peculiarities, subtleties, and unique requirements of research datasets. In this paper we probe into the key differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Face-to-face interviews; address aims 1 & 2, and is reported in [32] 3. Market appraisal and review; addresses aim 1, and is reported in [17,26] 4. A technical experiment comparing data retrieval (DR) with traditional information retrieval (IR); addresses aims 2 & 3, and is reported in [16] Methods 1 and 2 above (questionnaire and interview) were conducted sequentially, the purpose of the latter being chiefly to probe further into and expand upon some of the findings and hints from the former.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Face-to-face interviews; address aims 1 & 2, and is reported in [32] 3. Market appraisal and review; addresses aim 1, and is reported in [17,26] 4. A technical experiment comparing data retrieval (DR) with traditional information retrieval (IR); addresses aims 2 & 3, and is reported in [16] Methods 1 and 2 above (questionnaire and interview) were conducted sequentially, the purpose of the latter being chiefly to probe further into and expand upon some of the findings and hints from the former.…”
Section: Methodsmentioning
confidence: 99%
“…In computing file sizes, we considered for text retrieval (research publications) only full research papers; and for data retrieval (research datasets), both the dataset itself and any documentation(s) it comes with. Detailed findings and discussions may be found in [16,17].…”
Section: A Technical Experiments Comparing Dr With Traditional Irmentioning
confidence: 99%
See 1 more Smart Citation